Pleural-Based Intrathoracic Cystic Lymphangioma in an Infant Mimicking a Pneumonia. (6th May 2019) - Frimer, Zev; Fink, Daniel; Cytter-Kuint, Ruth; Doviner, Victoria; Picard, Elie
Abstract : Cystic lymphangioma is an uncommon benign tumor that occurs primarily in children in the cervical region. We report the first case of a pleural-based cystic lymphangioma in an infant. The patient was admitted for RUL pneumonia. Because of the persistence of the radiographic findings despite clinical improvement, a computed tomography (CT) and a magnetic resonance imaging (MRI) scan were performed. They showed a multiloculated cystic lesion in the superior posterior right hemithorax. A surgical procedure was performed with complete resection of the tumor. Histopathological examination showed a pleural-based intrathoracic multicystic lymphangioma. One year after the surgery, the patient feels well without any sign of recurrence.